CARDIOFACIOCUTANEOUS SYNDROME (CFCS) IN THE LIGHT OF CONTEMPORARY RESEARCH - A REVIEW OF THE LITERATURE - Patrycja Walkiewicz,; Anna Rakoczy,; Gabriela Prucnal,; Jowita Frydrych,; Karolina Ochyra,; Karolina Ryba,; Katarzyna Znamirowska,; Klaudia Zacher,; Kornelia Pudło,; Martyna Bukała, (International Journal of Innovative Technologies in Social Science, 2025)
The term RASopathies was introduced to describe a group of genetic syndromes that share similar phenotypic features and a common molecular basis. RASopathies are among the most numerous groups of recognized congenital developmental disorders. These syndromes have variable clinical courses, and the phenotypic features observed in newborns may differ from those seen in later stages of life - childhood, adolescence, or adulthood - which significantly complicates accurate clinical diagnosis.  The underlying cause of these disorders involves mutations in genes encoding proteins associated with the Ras/MAPK (mitogen-activated protein kinase) signaling pathway. Cardiofaciocutaneous syndrome (CFCS) is a representative RASopathy, clinically defined by distinctive craniofacial dysmorphism, congenital heart defects, dermatological anomalies, postnatal growth retardation, and varying degrees of intellectual disability. Recent advances in molecular genetics have facilitated, at least to some extent, the differential diagnosis of CFCS, thereby improving diagnostic accuracy. Lifelong, multidisciplinary medical management is essential for both pediatric and adult patients, necessitating coordinated care involving specialists from various medical fields. This article focuses on the molecular pathogensis, clinical features, prenatal findings and recommended evaluations following initial diagnosis.Materials: We conducted a review and analysis of the literature available in the PubMed database, using keywords.